English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I can't figure this one out! Maybe help on how to solve it if you wish?

2007-01-03 11:27:30 · 4 answers · asked by Mikey 2 in Science & Mathematics Mathematics

4 answers

Given:
{xy = 2.25
{x+y = -3

to do this, get y = -x-3 and substitute into the first
x(-x-3) = 2.25
0 = x^2 + 3x + 2.25
(x+1.5)^2 = 0
the solution to x is -1.5
y = 1.5-3= -1.5

*** the correct solution is -1.5, -1.5 ***

2007-01-03 11:31:00 · answer #1 · answered by sesquipedalian 3 · 1 0

√2.25 = ± 1.5,
but for a general approach which does not require guessing,
xy = 2.25
x + y = - 3
x(-x - 3) = 2.25
x^2 +3x +2.25 = 0
x = (- 3 ± √(9 - 4*2.25))/2
x = (- 3 ± √(9 - 9))/2
x = -3/2
x = -1.5

2007-01-03 11:46:01 · answer #2 · answered by Helmut 7 · 1 0

Sum = 3
Product = 2,25
Thus,
( x + y = 3
(x* y = 2,25
x = 3 - y

(3 - y)y = 2,25
-y² + 3y -2,25 = 0
y² - 3y + 2,25 = 0
D = 3² - 4.1.2,25
d = 9 - 9 = 0

y = (3 +/- sqrt of 0) : 2 = 1,5
x + y = 3
x = 3 - 1,5
x = 1,5
Solution: (x,y) = (1,5; 1,5)
<>

2007-01-03 11:37:18 · answer #3 · answered by aeiou 7 · 0 2

-1.5 and -1.5

2007-01-03 11:32:57 · answer #4 · answered by strtat2 5 · 1 0

fedest.com, questions and answers